Nilotinib restores memory function by preventing dopaminergic neuron degeneration in a mouse model of Alzheimer's Disease. (July 2021) - La Barbera, Livia; Vedele, Francescangelo; Nobili, Annalisa; Krashia, Paraskevi; Spoleti, Elena; Latagliata, Emanuele Claudio; Cutuli, Debora; Cauzzi, Emma; Marino, Ramona; Viscomi, Maria Teresa; Petrosini, Laura; Puglisi- Allegra, Stefano; et al.
Highlights: Morphology and autophagic process are impaired in VTA DA neurons of Tg2576 mice. Tg2576 DA neurons show increased excitability and changes in neuronal conductances. Midbrain of Tg2576 mice shows increased activation of c-Abl tyrosine kinase. Nilotinib, a c-Abl inhibitor, ameliorates DA neuron loss and cell deficits. Nilotinib restores hippocampal DA levels and cognitive functions. Abstract: What happens precociously to the brain destined to develop Alzheimer's Disease (AD) still remains to be elucidated and this is one reason why effective AD treatments are missing. Recent experimental and clinical studies indicate that the degeneration of the dopaminergic (DA) neurons in the Ventral Tegmental Area (VTA) could be one of the first events occurring in AD. However, the causes of the increased vulnerability of DA neurons in AD are missing. Here, we deeply investigate the physiology of DA neurons in the VTA before, at the onset, and after onset of VTA neurodegeneration. We use the Tg2576 mouse model of AD, overexpressing a mutated form of the human APP, to identify molecular targets that can be manipulated pharmacologically. We show that in Tg2576 mice, DA neurons of the VTA at the onset of degeneration undergo slight but functionally relevant changes in their electrophysiological properties and cell morphology. Importantly, these changes are associated with accumulation of autophagosomes, suggestive of a dysfunctional autophagy, and with enhanced activation of c-Abl, a tyrosine kinase previously implicated in the pathogenesis of neurodegenerative diseases. Chronic treatment of Tg2576 mice with Nilotinib, a validated c-Abl inhibitor, reduces c-Abl phosphorylation, improves autophagy, reduces Aβ levels and – more importantly – prevents degeneration as well as functional and morphological alterations in DA neurons of the VTA. Interestingly, the drug prevents the reduction of DA outflow to the hippocampus and ameliorates hippocampal-related cognitive functions. Our results strive to identify early pathological brain changes in AD, to provide a rational basis for new therapeutic interventions able to slow down the disease progression.